Mitochondria-targeting near-infrared light-triggered thermosensitive liposomes for localized photothermal and photodynamic ablation of tumors combined with chemotherapy. Issue 31 (25th July 2017) - Yue, Caixia; Yang, Yuming; Song, Jie; Alfranca, Gabriel; Zhang, Chunlei; Zhang, Qian; Yin, Ting; Pan, Fei; de la Fuente, Jesús M.; Cui, Daxiang
Abstract : Lonidamine, an anticancer drug that acts on mitochondria, has poor water solubility. Abstract : Lonidamine, an anticancer drug that acts on mitochondria, has poor water solubility. Mitochondria are the primary source of cellular reactive oxygen species (ROS), which are necessary for photodynamic therapy. Hence, a mitochondria-targeting drug delivery system loaded with Lonidamine and a ROS-produced photosensitizer could improve the bioavailability of Lonidamine and maximize photodynamic therapeutic efficiency. Here we report, for the first time, new IR-780 and Lonidamine encapsulated mitochondria-targeting thermosensitive liposomes (IL-TTSL). DSPE-PEG2000-NH2 was coupled with triphenylphosphine to form DSPE-PEG2K -TPP. The liposomes (IL-TTSL) were self-assembled from DPPC, DSPC, DSPE-PEG2K -TPP, cholesterol, IR-780 and Lonidamine. Coupled linker modified triphenylphosphine (TPP) is cationic and can selectively accumulate several hundred-fold within mitochondria. Once the liposomes are located inside mitochondria, 808 nm laser irradiation could trigger photosensitizer IR-780 to elevate the local temperature, which could be utilized in photothermal therapy and induce the release of Lonidamine from the thermosensitive liposomes. Meanwhile, IR-780 could release ROS for photodynamic therapy in mitochondria and increase photodynamic therapeutic efficiency. Our results showed that the surface modification of the liposomes with triphenylphosphine cations had good mitochondria-targeting ability. The liposomes exhibited good biocompatibility and all components of the empty liposomes were safe to be used in humans. Few reports were related to IR-780 being used in photodynamic therapy and we proved this function of IR-780. Overall, the stealth liposomes provide a promising new strategy to realize mitochondria-targeting thermosensitive chemo-, photodynamic and photothermal combination therapy with a single light source for lung cancer.